E-commerce website service quality and customer loyalty using WebQual 4.0 with importance performances analysis, and structural equation model: An empirical study in Shopee - Wijaya, I Gusti Ngurah Satria; Triandini, Evi; Kabnani, Ezra Tifanie Gabriela; Arifin, Syamsul (Register: Jurnal Ilmiah Teknologi Sistem Informasi, 2021)
The rapid growth of business models in the form of online shops, Business to Consumer (B2C) and the Consumer to Consumer (C2C) concept, has an impact in the form of intense competition between online business owners. It is not easy to find a solution to this problem. The owner must provide good or even excellent service by improving the website quality so that customers can achieve satisfaction and loyalty. This research aimed to specify the influence of website quality on customer loyalty with satisfaction as an e-commerce website moderation variable and to investigate the WebQual 4.0 attributes that affect this relationship of the model. This study used 104 respondents of Shopee Consumer and analyzed with the WebQual with Importance Performance Analysis (IPA) method and Structural Equation Model (SEM). The result is that the service quality variable significantly influence e-commerce website customer satisfaction variable, customer satisfaction variable has no significant effect on e-commerce website customer loyalty variables, and website service quality variable significantly influence e-commerce website customer loyalty variable. The attributes of WebQual 4.0 that need to be considered by e-commerce management to impact the level of user satisfaction and customer loyalty are â€œdesign by the type of websiteâ€, â€œprovide simple-to-understand informationâ€, â€œprovide information following the formatâ€, â€œfeel safe to complete transactionsâ€, â€œthe website makes the positive/absolute experience for meâ€, and â€œprovide detailed informationâ€. The research implications can be taken into consideration for e-commerce management.